2020
DOI: 10.3390/genes11091038
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Imprinted microRNAs and Their RNA Targets

Abstract: Mammalian genomes contain many imprinted microRNAs. When an imprinted miRNA targets an unimprinted mRNA their interaction may have different fitness consequences for the loci encoding the miRNA and mRNA. In one possible outcome, the mRNA sequence evolves to evade regulation by the miRNA by a simple change of target sequence. Such a response is unavailable if the targeted sequence is strongly constrained by other functions. In these cases, the mRNA evolves to accommodate regulation by the imprinted miRNA. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 112 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…The evolutional role and constraint can be considered another point of view of imprinted miRNAs [ 184 , 185 , 186 ]. It was suggested that imprinted noncoding RNAs was under distinctive selective forces when regulating transcripts of the allele inherited from the other parent [ 184 , 185 , 186 , 187 ]. Accordingly, when an mRNA had sequence complementary to an imprinted miRNA, the complementary miRNA-mRNA sequences pair originated from different alleles.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The evolutional role and constraint can be considered another point of view of imprinted miRNAs [ 184 , 185 , 186 ]. It was suggested that imprinted noncoding RNAs was under distinctive selective forces when regulating transcripts of the allele inherited from the other parent [ 184 , 185 , 186 , 187 ]. Accordingly, when an mRNA had sequence complementary to an imprinted miRNA, the complementary miRNA-mRNA sequences pair originated from different alleles.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This can be considered a communication between the maternal and paternal alleles, hence the two alleles coordinate their activities [ 186 ]. The kinship theory considers genomic imprinting as a mechanism to change gene dosage, because it has a differential effect on the fitness of matrilineal and patrilineal relatives [ 184 , 185 , 186 , 187 ]. Additionally, Haig and Mainieri suggested that when an imprinted miRNA targets an unimprinted mRNA, their interaction may have different fitness consequences for the loci encoding the miRNA and mRNA [ 184 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins are a more expressive language than RNA. However, this relegation of RNA to the role of a messenger between DNA text and protein performance neglects the central roles that ‘non-coding’ RNAs continue to play in information-processing within cells (Mainieri & Haig, 2018 , 2019 ; Haig & Mainieri, 2020 ).…”
Section: Text and Performancementioning
confidence: 99%